Amateur boxing and risk of chronic traumatic brain injury: systematic review of observational studies - Loosemore, M.; Knowles, C. H.; Whyte, G. P. (British Journal of Sports Medicine, 2008)
Objective: To evaluate the risk of chronic traumatic brain injury from amateur boxing. Setting: Secondary research performed by combination of sport physicians and clinical academics. Design, data sources, and methods: Systematic review of observational studies in which chronic traumatic brain injury was defined as any abnormality on clinical neurological examination, psychometric testing, neuroimaging studies, and electroencephalography. Studies were identified through database (1950 to date) and bibliographic searches without language restrictions. Two reviewers extracted study characteristics, quality, and data, with adherence to a protocol developed from a widely recommended method for systematic review of observational studies (MOOSE). Results: 36 papers had relevant extractable data (from a detailed evaluation of 93 studies of 943 identified from the initial search). Quality of evidence was generally poor. The best quality studies were those with a cohort design and those that used psychometric tests. These yielded the most negative results: only four of 17 (24%) better quality studies found any indication of chronic traumatic brain injury in a minority of boxers studied. Conclusion: There is no strong evidence to associate chronic traumatic brain injury with amateur boxing.